Microtiter Screening Reveals Oxygen-Dependent Antimicrobial Activity of Natural Products Against Mastitis-Causing Bacteria - Ferguson, Scott A.; Menorca, Ayana; Van Zuylen, Essie M.; Cheung, Chen-Yi; McConnell, Michelle A.; Rennison, David; Brimble, Margaret A.; Bodle, Kip; McDougall, Scott; Cook, Gregory M.; Heikal, Adam (Frontiers in Microbiology, 2019)
In this study we investigated the influence of oxygen availability on a phenotypic microtiter screen to identify new, natural product inhibitors of growth for the bovine mastitis-causing microorganisms; Streptococcus uberis, Staphylococcus aureus, and Escherichia coli. Mastitis is a common disease in dairy cattle worldwide and is a major cause of reduced milk yield and antibiotic usage in dairy herds. Prevention of bovine mastitis commonly relies on the application of teat disinfectants that contain either iodine or chlorhexidine. These compounds are used extensively in human clinical settings and increased tolerance to chlorhexidine has been reported in both Gram-positive and Gram-negative microorganisms. As such new, non-human use alternatives are required for the agricultural industry. Our screening was conducted under normoxic (20% oxygen) and hypoxic (<1% oxygen) conditions to mimic the conditions on teat skin and within the mammary gland respectively, against two natural compound libraries. No compounds inhibited E. coli, under either oxygen condition. Against the Gram-positive microorganisms, 12 inhibitory compounds were identified under normoxic conditions, and 10 under hypoxic conditions. Data revealed a clear oxygen-dependency amongst compounds inhibiting growth, with only partial overlap between oxygen conditions. The oxygen-dependent inhibitory activity of a naturally occurring quinone, beta-lapachone, against S. uberis was subsequently investigated and we demonstrated that this compound is only active under normoxic conditions with a minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of 32 µM and kills via a reactive oxygen species (ROS)-dependent mechanism as has been demonstrated in other microorganisms. These results demonstrate the importance of considering oxygen-availability in high-throughput inhibitor discovery.